Cross-country skiing on force-measuring treadmill - Kehler, A.; Haijkova, E.; Holmberg, H. C.; Kram, R. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this experiment was to validate a FTM as an effective tool for future cross-country ski research and to further analyze the ground reaction forces during diagonal stride skiing. We asked two questions: